ANALISIS SEBARAN LOKASI STASIUN PENGISIAN BAHAN BAKAR UMUM (SPBU) DI KABUPATEN GORONTALO (Distribution Analysis of The Location of Public Fuel Filling Stations (SPBU) in Gorontalo District) - Almijan Yusuf; Arthur Gani Koto (Jurnal Sains Informasi Geografi, 2020)
Gorontalo District, which is geographically located in the middle of Gorontalo Province and is traversed by the Trans Sulawesi road, is the main transportation route from Central Sulawesi, Pohuwato Regency and Boalemo Regency to the east, as well as from North Sulawesi Province, Gorontalo City and Bone Bolango Regency to the west. The mobility of the vehicle that passes every time requires the consumption of fuel oil (BBM). The supply of BBM by Pertamina through the Public Fuel Filling Station (SPBU) is one of the main infrastructure available. The purpose of this study is to examine the spatial distribution of gas stations in Gorontalo District. The navigation measurement tool in the form of GPS is used to take the coordinates of gas stations based on field checks. Nearest neighbor analysis method is used to calculate the distribution pattern of location points between gas stations. The results showed that the distribution of SPBU location points in Gorontalo District formed a uniform (linear) pattern and the location distance between SPBUs was included in the very far criteria.